3D Exoscopic Surgery (3Des) for Transoral Oropharyngectomy - Crosetti, Erika; Arrigoni, Giulia; Manca, Andrea; Caracciolo, Alessandra; Bertotto, Ilaria; Succo, Giovanni (Frontiers in Oncology, 2020)
Over the past three decades, the incidence of oropharyngeal squamous cell carcinoma has increased, primarily related to the spread of human papillomavirus. Treatment has always been preferentially unimodal (surgery or radiotherapy) for early stage disease and multimodal (surgery with adjuvant therapy or concomitant chemoradiotherapy) for advanced stages. Recently, the surgical approach has gained renewed interest due to the morbidity of non-surgical treatments and also to technical innovations. We have coined the term 3Des (3D exoscope surgery) to describe the use of the 3D Vitom Exoscope System for transoral surgery of oropharyngeal cancers. During the period from June 2017 to May 2018, 10 patients with oropharyngeal cancer were treated by oropharyngeal surgery with the 3Des approach at FPO IRCCS Institute of Candiolo. The aim of the present prospective study was to evaluate the utility of 3Des for the treatment of early-stage oropharyngeal cancer. 3Des could represent a viable alternative to the operating microscope and robotic surgery thanks to its excellent ability to provide 3D visual information, depth of field, magnification, image contrast, color imaging, and low running costs. It promises great utility in the learning process, with the possibility of recording in high definition.